2015
DOI: 10.3389/fmicb.2015.00745
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promotion induced by phosphate solubilizing endophytic Pseudomonas isolates

Abstract: The use of plant growth promoting bacterial inoculants as live microbial biofertilizers provides a promising alternative to chemical fertilizers and pesticides. Inorganic phosphate solubilization is one of the major mechanisms of plant growth promotion by plant associated bacteria. This involves bacteria releasing organic acids into the soil which solubilize the phosphate complexes converting them into ortho-phosphate which is available for plant up-take and utilization. The study presented here describes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
299
1
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 568 publications
(359 citation statements)
references
References 49 publications
15
299
1
21
Order By: Relevance
“…Although rhizobacteria are the most promising as biofertilizers, phosphate solubilizing endophytic bacteria are also described. Oteino et al (2015) demonstrated that the inoculation of endophytes into the rhizosphere increased growth in plants suffering from limited phosphate supply.…”
Section: Resultsmentioning
confidence: 99%
“…Although rhizobacteria are the most promising as biofertilizers, phosphate solubilizing endophytic bacteria are also described. Oteino et al (2015) demonstrated that the inoculation of endophytes into the rhizosphere increased growth in plants suffering from limited phosphate supply.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies Pseudomonas, Bacillus, Rhizobium, Micrococcus and Erwinia are reported as phosphate solubilizer bacteria (Rodriguez and Fraga, 1999). Pseudomonas and Bacillus have been screened inorganic phosphate solubilizing isolates from Pisumsativum L. plants (Oteino et al, 2015). Among the reported phosphate solubilizing bacteria, Bacillus and Pseudomonas are the most important bacteria (Chauhan et al, 2013;Sharma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of utilizing P‐liberating bacteria in agricultural systems is that they can have synergistic beneficial effects, for example, pathogen suppression (Vassilev et al ., 2006). The majority of research into P mobilization by PGPR has focused on the solubilization of inorganic P through acidification of the surrounding soil via the release of organic acids, namely gluconic acid (Rodrı'guez and Fraga, 1999; Miller et al ., 2010; Oteino et al ., 2015). The genus Pseudomonas represents one soil bacterial group that is frequently associated with plant‐growth promotion, including P solubilization (Miller et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%